Uncommon Movement Disorders in Chronic Hepatic Disease with Response to Rifaximin. (2nd August 2019) - Sousa, Ana L.; Salgado, Paula; Alves, José E.; Silva, Sara; Ferreira, Sofia; Magalhães, Marina
Background: Chronic hepatic disease can present with extrapyramidal symptoms. We describe two cases that presented with highly unusual movement disorders: ballism and gait freezing. Case report: Patient 1 is a 42-year-old man with previous episodes of hepatic encephalopathy (HE) who presented with upper limb dystonia and generalized chorea that progressed to ballism. Patient 2 is a 55-year-old woman who presented with pronounced gait freezing. In both patients, features of HE and acquired hepatocerebral degeneration coexisted. They improved markedly, though transiently, with rifaximin. Discussion: Ammonia-reducing treatments should be considered in patients presenting with movement disorders due to chronic liver disease.